Differential Effects of Input-based and Output-based Tasks on L2 Vocabulary Learning - Duong, Phuong-Thao; Montero Perez, Maribel; Desmet, Piet; Peters, Elke (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée)

(untitled) (University of New Brunswick, 2021)
This paper reports on a quasi-experimental study that explored the differential effects of input- and output-based tasks on L2 vocabulary learning. The study adopted a pretest- posttest within-participants design, with sixty Vietnamese EFL university students. Participants in the experimental group completed four input and four output tasks in an online learning environment. The target items (ten single words and ten compounds) were counterbalanced across the tasks. The study measured vocabulary gains at four levels of sensitivity: spontaneous use of the target items, form recall, meaning recall and meaning recognition. The analyses showed that the input-based tasks resulted in higher vocabulary gains at the meaning recall level, whereas the output-based tasks resulted in better scores at the form recall level. No difference was found in the spontaneous use and meaning recognition tests.